Protected cultivation — the technology for future - Dutt, Som (Indian Horticulture, 2019)
Introduction: The Indian Society for Protected Cultivation (ISPC) organized a National Seminar on ‘Advances in Protected Cultivation’ at the NASC Complex, DPS Marg, Pusa, New Delhi, on 21 March 2013, with an objective of collection and collation of scientific advances made in protected cultivation in India and dissemination of these among policy-planners, farmers, students, scientists, industry and other stakeholders.